2011
DOI: 10.1371/journal.pone.0023728
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Changes in QTc Duration during In-Hospital Haloperidol Use

Abstract: AimsTo evaluate changes in QT duration during low-dose haloperidol use, and determine associations between clinical variables and potentially dangerous QT prolongation.MethodsIn a retrospective cohort study in a tertiary university teaching hospital in The Netherlands, all 1788 patients receiving haloperidol between 2005 and 2007 were studied; ninety-seven were suitable for final analysis. Rate-corrected QT duration (QTc) was measured before, during and after haloperidol use. Clinical variables before haloperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
4
22
0
1
Order By: Relevance
“…As in studies conducted in acute settings, we found that benzodiazepines were the PRN drugs most commonly prescribed but that antipsychotic prescriptions were also common, particularly Haloperidol. This is despite Haloperidol's propensity to cause extra-pyramidal side effects and prolongation of QTc interval (Blom et al, 2011). Its popularity may be due to the fact that it can be administered IM as well as orally and can be given at the same time as IM Lorazepam, unlike IM Olanzapine.…”
Section: Discussionmentioning
confidence: 99%
“…As in studies conducted in acute settings, we found that benzodiazepines were the PRN drugs most commonly prescribed but that antipsychotic prescriptions were also common, particularly Haloperidol. This is despite Haloperidol's propensity to cause extra-pyramidal side effects and prolongation of QTc interval (Blom et al, 2011). Its popularity may be due to the fact that it can be administered IM as well as orally and can be given at the same time as IM Lorazepam, unlike IM Olanzapine.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, sudden cardiac deaths, though uncommon, have been associated with long-term treatment with older as well as modern antipsychotic drugs, and unanticipated cardiac arrhythmias may contribute to this risk [ 99,140,171,172 ] ; decreased mortality also has been reported in association with long-term antipsychotic treatment [ 206 ] . Prolongation of the QTc interval is especially likely with thioridazine or mesoridazine more than haloperidol among older neuroleptics, somewhat less with ziprasidone, and apparently negligibly with clozapine among second-generation antipsychotics [ 4,26,81 ] . Taken alone, short of severe acute overdoses, such responses to these agents are not likely, but risk increases as additional agents with inhibitory effects on cardiac repolarization are added, including tricyclic antidepressants and class Ia, sodium-channel blocking, antiarrhythmic drugs such as quinidine, procainamide (Pronestyl ® ), and disopyramide (Norpace ® ), or if other risk factors are present.…”
Section: Cardiac Risks and Sudden-deathmentioning
confidence: 99%
“…Evidence from cohorts of palliative care and hospital inpatients treated with haloperidol suggests that severely prolonged QTc intervals (>500 ms) are rare, occurring in less than 1% of patients. 106,112 Future studies of antipsychotic drug treatment and prophylaxis should incorporate ECG monitoring for QTc prolongation. 102 …”
Section: Resultsmentioning
confidence: 99%